SYSTEM OF INTELLECTUAL DEVELOPMENT OF STUDENTS IN FOREIGN LANGUAGE CLASSES - Qobulova, Dildora (Журнал иностранных языков и лингвистики, 2022)
This article is about implementing system of intellectual development of students in foreign language classes.